Savāniḥ Qāsimī : yaʻnī, sīrat-i Sayyidnā al-Imāmulkabīr Shamsulislām Ḥaz̤rat Maulānā Muḥammad Qāsim al-Nānautvī - Gīlānī, Sayyid Manāẓar Aḥsan (SAMP early 20th-century Indian books project, 1953)
On the life of Muḥammad Qāsim Nānautvī, Indian Muslim scholar.